Preliminary investigation of the pharmacology of the human internal anal sphincter. Issue 8 (August 1969) - Parks, A. G.; Fishlock, D. J.; Cameron, J. D. H.; May, H.
Abstract : The smooth muscle from the human internal anal sphincter has been investigated pharmacologically in vitro. The upper and lower parts of the sphincter responded to catecholamines in a similar manner. Noradrenaline caused contraction which could be antagonized by phenoxybenzamine. After phenoxybenzamine, noradrenaline caused relaxation which could be blocked by pronethalol. Isoprenaline caused relaxation which could be specifically prevented by pronethalol. Adrenaline was variable in its effect: low concentrations caused relaxation and high concentrations caused contraction. It is suggested that the anal smooth muscle contains α-adrenergic receptors subserving contraction and β-receptors subserving relaxation. The lower part of the sphincter was generally insensitive to acetylcholine and nicotine whereas the upper part of the sphincter contracted with acetylcholine and regularly relaxed with nicotine. The nicotine response was antagonized by hexamethonium, procaine, and pronethalol. It is suggested that nicotine stimulated some part of the nervous mechanism in the upper part of the sphincter and that a catecholamine was the mediator of the inhibitory response.